INVESTIGATION OF OSCILLATIONS ARISING IN SUBSIDING SOILS DURING COMPACTION OF BY THEIR DEEP EXPLOSIONS - Dmitriy Mihailovich Steshenko; Vitaliy Viktorovich Serbin; Bagratik Aramaisovich Parsyan (Вестник Северо-Кавказского федерального университета)
Level of vibration is investigated from deep explosions in collapsible soils, the analysis of amplitude decay with distance from an explosion point is carried out, the preliminary forecast of influence of explosion for build-ings and constructions according to existing norms is made.